Cone-beam computed tomography as a surgical guide to impacted anterior teeth - Jeremias, Fabiano [UNESP]; Fragelli, Camila Maria Bullio [UNESP]; Mastrantonio, Simone Di Salvo [UNESP]; Dos Santos-Pinto, Lourdes [UNESP]; Santos-Pinto, Ary Dos [UNESP]; Pansani, Cyneu Aguiar [UNESP] (Wolters Kluwer, 2016)
Surgical procedure for removal of impacted teeth is a challenge for clinicians as it involves accuracy in the diagnosis and localization of the dental elements. The cone-beam computed tomography (CBCT), compared to the conventional radiography, has a greater potential to provide complementary information because of its three-dimensional (3D) images, reducing the possibility of failures in surgical procedures. Two 10-year-old boys presented with aesthetic issues associated with the juxtaposition of ectopic teeth with the permanent ones. Both two-dimensional and 3D preoperative radiographic diagnostic sets were produced. The occlusal and panoramic radiographs were not enough for proper localization of impacted incisors. Thus, the CBCT was used as a surgical guide. After 2 years of longitudinal following, no lesion was recorded, and the orthodontic treatment has proven successful. In all cases, CBCT contributed to both diagnosis and correct localization of supernumerary teeth, aiding the professional in the treatment planning, and consequently in the clinical success. The surgeries were completely safe, avoiding damage in noble structures, and providing a better recovering of the patients.
Keywords: Cone-beam computed tomography; diagnosis; impacted tooth